Design, synthesis, and neuroprotective effects of dual‐brain targeting naproxen prodrug. Issue 5 (22nd March 2018) - Wang, Linhui; Zhang, Li; Zhao, Yi; Fu, Qiuyi; Xiao, Wenjiao; Lu, Runxin; Hai, Li; Guo, Li; Wu, Yong
Abstract: A new dual‐targeting naproxen prodrug conjugated with glucose and ascorbic acid for central nervous system (CNS) drug delivery was designed and synthesized in order to effectively deliver naproxen to the brain. Naproxen could be released from the prepared prodrugs when incubated with various buffers, mouse plasma, and brain homogenate. Also, the prodrug showed superior neuroprotective effect in vivo over naproxen. Our results suggest that chemical modification of therapeutics with warheads of glucose and ascorbic acid represents a promising and efficient strategy for the development of brain targeting prodrugs by utilizing the endogenous transportation mechanism of the warheads. Abstract : A new dual‐targeting naproxen prodrug conjugated with glucose and ascorbic acid for central nervous system drug delivery was designed and synthesized. The prodrug showed superior neuroprotective effect in vivo compared to naproxen. Chemical modification of therapeutics with glucose and ascorbic acid is revealed as a promising strategy for the development of brain‐targeting prodrugs.